Are we really surmounting the binary? Visualizing race and ethnicity group relations via embedded relational diagrams - Rima Wilkes; Aryan Karimi (Frontiers in Sociology)
Social theories explain the current state of affairs between social groups. In the sociological race literature, theories traditionally explained White-Black relations. In the ethnicity literature, theories explained native-born and immigrant relations. What happens to social theorizing of current group relations when new third groups emerge in society? Because social reconfigurations unfold in the longue durée and are less amenable to controlled tests, social sciences are still in the process of theorizing the effects of third groups on the old racial and ethnic relations. To outline the theorizing process, its elements, and its challenges, we propose a novel embedded relational visual diagram of the triadic relationship between Asian American, Black American, and White American groups. We use a range of six theories from the race and ethnicity literature as case studies to illustrate the applicability of the visualizing method. We show why these triadic social relations inevitably collapse into a new social duality.